Method of auditing in conditions of martial law - Lubenchenko, O.; Лубенченко, О.; Shulga, S.; Шульга, С.; Pavlova, Halyna; Павлова, Галина Євгеніївна (Walter de Gruyter, 2023)
In the article there are considered methodical recommendations on the actions of auditors during martial law. They relate to such stages of the audit as the preparatory phase, the planning phase, the task implementation and the final phase. The preparatory stage requires the identification of the client and the conclusion of an audit agreement. Under martial law, new risks are emerging, systematized by the authors and related to the identification of persons involved in terrorist activities and the proliferation of weapons of mass destruction. The systematization of risks and the use of IT technologies to identify and verify the client allows auditors, as specially designated entities of primary financial monitoring, to identify and freeze the assets of such persons in a timely manner and stop providing any services. At the client acceptance and assignment stage, auditors assess ethical threats. As a result, a working paper has been developed to assess ethical threats in the light of martial law. At the planning stage, special attention should be paid to reviewing risks, namely how military aggression affects the continuity of any business. Clarification of risk factors for termination allows you to plan audit procedures to gather audit evidence and further determine the auditor's opinion on continuity (opinion with an explanatory paragraph, opinion with a reservation, negative opinion, disclaimer of opinion). One of the effective procedures for collecting audit evidence at the stage of the task is inventory. У статті розглянуто методичні рекомендації щодо дій аудиторів під час воєнного стану. Вони стосуються таких етапів аудиту, як підготовчий етап, фаза планування, виконання завдання і завершальна фаза. Підготовчий етап вимагає ідентифікація клієнта та укладення договору на проведення аудиту. В умовах воєнного стану, виникають нові ризики, систематизовані авторами та пов’язані з ідентифікацією осіб, причетних до терористичної діяльності та розповсюдження зброї масового ураження. Систематизація ризиків та використання ІТ-технологій для ідентифікації та верифікації клієнта дозволяє аудиторам як спеціально уповноваженим суб’єктам первинного фінансового моніторингу ідентифікувати та своєчасно заморозити активи таких осіб та припинити надання будь-яких послуг. На етапі прийняття та призначення клієнта аудитори оцінюють етичні загрози. В результаті, розроблено робочий документ для оцінки етичних загроз у світлі воєнного стану. На етапі планування особливу увагу слід приділити перегляду ризиків, а саме того, як військова агресія впливає на безперебійність будь-якого бізнесу. Уточнення факторів ризику дозволяє планувати аудиторські процедури для збору аудиторських доказів і подальшого визначення висновок аудитора про безперервність (висновок з пояснювальним пунктом, висновок застереження, негативна думка, відмова від думки). Одна з ефективних процедур збір аудиторських доказів на етапі завдання полягає в інвентаризації.
Методика аудиту в умовах воєнного стану
Keywords: war; війна; risk; ризик; business entities; суб'єкти господарювання